Preparing Students of the Institute of Physical Education and Sport to Use Distant Learning Technologies in the Course of Pandemic - Olesov, Nikolai P. (2020)
This study reveals the importance of distance learning for professional students’ training in this innovative activity in regional institute of physical education. The urgency of research is based on the problem of insufficient readiness of physical education teachers and sports coaches in the Republic of Sakha (Yakutia) to implement distance learning. It is also based on the lack of widely used educational programs that are scientifically grounded, well tested in practice and that promote targeted training of physical education teachers to use DL technologies in the course of pandemic. The experiment involved bachelors’ and masters’ degree students in various specialties from the M.K. Ammosov North-Eastern Federal University (NEFU) and the Churapchinsky State Institute of Physical Education and Sport. All the students were majoring in Pedagogical Education and Physical Education. The leading method of research into the problem is the use of mathematical statistics to monitor the dynamics of the process development of training future physical education teachers and sports coaches to use DL technology. Main findings: The research results show that the use of new types of educational activities in the course of pandemic contributes to the effective contemporary professional training of Physical Education teachers and sports coaches.The practical implications of the research may be found in the analysis of future Physical Education teachers’ training to use DL in conditions of remote excess to the educative process of the discipline “Information Technologies in Physical Education and Sports” study. The content of the article will be useful for faculty members of institutions of higher education, institutions of additional education, and physical education teachers. The originality of this study is in providing the facts that the high proficiency and professional capacity of graduates of physical culture institutes, their ability and competence to adjust the accumulated knowledge and skills to new goals and objectives of education, regularly changing conditions of professional activity can be formed and developed through the effective use of DL technologies. adapted to the solution of occupational tasks.